Proceedings of the 1st International Conference on Social, Applied Science and Technology in Home Economics (ICONHOMECS 2017) 2018
DOI: 10.2991/iconhomecs-17.2018.13
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation Of Entrepreneurship Education And Production Unit In Vocational High Schools

Abstract: Production unit in vocational high schools is a place to train students with entrepreneurship practice. Teachers utilize this unit to help students developing competence in production lesson. Research uses quantitative approach. Subject includes 40 teachers of cloth-making lesson in vocational high schools of East Java. Data collection method is documentation and questionnaire with Likert Scale entailing five answer alternatives. Data analysis technique involves T-Test and Explanatory Factor Analysis. Some fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 4 publications
0
1
0
Order By: Relevance
“…Teachers can utilize production unit to help pupils develop competence in production lessons. Marniati et al (2018) found that practice-based activities at production unit in schools were more effective than same activity in modest industries. Herry et al (2016) recommended the establishment of production unit managers who can do planning, implementation guides, supervision and monitoring the activities and roles of teachers and pupils.…”
Section: A Production Unit In Schoolsmentioning
confidence: 97%
“…Teachers can utilize production unit to help pupils develop competence in production lessons. Marniati et al (2018) found that practice-based activities at production unit in schools were more effective than same activity in modest industries. Herry et al (2016) recommended the establishment of production unit managers who can do planning, implementation guides, supervision and monitoring the activities and roles of teachers and pupils.…”
Section: A Production Unit In Schoolsmentioning
confidence: 97%
“…Additionally, intensive marketing campaigns are required in order that the workshop can operate successfully and get bulk orders in such a way that more students can be involved in the workshop. The researh by Marniati et al, (2018) shows that marketing products of the production unit may produce some benefits, increase the income of the school and school staff, help upgrade equipment and facilities for learning activities at class and in production units.…”
Section: Alumni Taking Entrepreneurial Actionsmentioning
confidence: 99%
“…The provision of skilled and educated workforce depends highly on the quality of education and training, especially those of vocational schools (Mahfud, 2013). Vocational High Schools (VHSs) are the institutions which are expected to develop and provide excellent human resources and skilled workers (Marniati et al, 2018). However, the fact shows that not all vocational graduates are absorbed in the industrial world, which causes a number of vocational graduates to get jobs outside the area of their expertise (Qotimah et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations